2008
DOI: 10.3349/ymj.2008.49.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis as a Risk Factor for Preterm Low Birth Weight

Abstract: PurposeThere is growing evidence showing that a number of complex human diseases are caused or are at least influenced by periodontal diseases. Such diseases include cardiovascular diseases, respiratory diseases, diabetes mellitus and osteoporosis. The aim of study was to evaluate periodontal diseases as a risk factor for a preterm low birth weight.Materials and MethodsA total of 48 mothers, 20 of who had a preterm low birth weight delivery, were examined in the Clinics of Periodontology, Faculty of Dentistry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 23 publications
0
26
0
3
Order By: Relevance
“…Offenbacher and his group in 1996 reported a sevenfold increased risk of a mother with periodontal disease delivering a PTLBW baby [15]. This observation was difficult to ignore and since then many studies have been completed but with varying results [16,17].…”
Section: Obsterics Outcomesmentioning
confidence: 99%
“…Offenbacher and his group in 1996 reported a sevenfold increased risk of a mother with periodontal disease delivering a PTLBW baby [15]. This observation was difficult to ignore and since then many studies have been completed but with varying results [16,17].…”
Section: Obsterics Outcomesmentioning
confidence: 99%
“…Smoking during pregnancy has been linked to 20-30% of LBW births and 10% of fetal and infant deaths (Boutigny et al, 2005). Infection is also considered as a major cause of PLBW deliveries, accounting for 30% and 50% of all cases (Offenbacher et al, 1998;Marakoglu et al, 2008). It has been proposed that one important factor contributing to the continuing prevalence of infants with PLBW is the effect of maternal burden of infection.…”
Section: Periodontal Disease and Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…The relationship between periodontal bacteria and systemic diseases was investigated extensively during the past two decades. More recently, a wealth of epidemiological, clinical and laboratory studies have provided irrefutable evidence that periodontal disease negatively impacts systemic health and proposed mechanisms by which such an association may occur (Fisher et al, 2008;Marakoglu et al, 2008). It is now widely accepted that periodontitis can induce pro-inflammatory cytokines, chemokines and mediators which may play a major role in the development of a variety of systemic conditions (Kuo et al, 2008).…”
Section: Look To Thy Mouth; Diseases Enter Here -George Herbert (1593mentioning
confidence: 99%
“…Association was found by Marakoglu et al The study results indicated that Periodontitis (OR: 3.6 95% CI: 1.06-12.18) together with bacterial vaginosis (OR: 11.57 95% CI: 1.26-105.7) were independent risk factors of a preterm low birth weight. 19 Further analysis was done to study any association of periodontal infection and bacterial vaginosis with perinatal outcomes. Majority of the newborns had an apgar of 9 at 1 minute (97.4%).…”
Section: Demographic Datamentioning
confidence: 99%